Pembentukan H2S Pada Proses Asidogenesis Limbah Cair Produksi Minyak Sawit - M Kamal Syah; David Andrio; Nina Veronika (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Palm oil mill effluent (POME) had characteristics to COD, BOD, and protein a sequence of 40.823 mg/L, 15.309 mg/L, 40.500, 58,22 mg/L. pH was influenced the acidogenesis stage in anaerobic process. Additionally, in the stage of acidogenesis H2S was formed compounds, coused odor, inhibit bacterial growth, and corrosion on metal. The control of pH (acid, neutral and alkali) was required in order to optimize the formation of volatile fatty acids and inhibit the formation of H2S. This research is aimed to know the influence of pH and the detention time towards the elimination of H2S and know the influence of pH and the detention time of the formation of volatile acid and H2S. This research was conducted by varying pH the range of 4-4,5 (acid); 7-7,5 (neutral); 8-8.5 (alkali). The result of the research showed the lowest formation of H2S is on acids’ pH with the concentration of formation as much as 0,37 mg/L/hari and the detention time 120 hours. The highest formation of TAV was produced on acids’ pH (4-4,5) with the concentration rate of formation as much as 1.739,45 mg/L, and efficiency elimination 40,05 %. %. It can be concluded pH optimum of inhibhit the formation H2S is pH alkali. While pH optimum the formation TAV is pH acid. Keywords : H2S, total volatile fatty acid, acidogenic, POME